Development of Innovative Learning Resources based on Isolation Materials Compound Purification and Identification Alkaloid Group - Ester Hartina Ria Sinaga (International Journal of Science and Applied Science: Conference Series, 2021)
This study aims to develop project-based innovative learning resources on purification isolation materials and identification of alkaloids using Flipbook Maker software based on SNPT. This research is a development research (R & D) with ADDIE model. The sample in this study were 3 lecturers at the State University of Medan, Faculty of Mathematics and Natural Sciences, majoring in Chemistry, as validators of media experts and the material was adjusted to the needs. The research instrument was an SNPT questionnaire filled out by media expert validators and material expert validators. Data were analyzed descriptively qualitatively. The results of the study indicate that project-based innovative learning resources on purification isolation materials and identification of alkaloid group compounds with an average score of 3.73 and categorized in the "Very feasible" criteria are used for purification isolation materials and identification of alkaloid group compounds in organic analytical chemistry learning.